Relationship between Perceptual and Motor Abilities on Fundamental Basketball Skills in 8-13 Years Old Children - Pavlidou Στεφανία; Michalopoulou Μαρία; Aggeloussis Νικόλαος; Kioumourtzoglou Ευθύμιος (Inquiries in Physical Education and Sport, 2006)
The purpose of the present study was to investigate differences in specific perceptual and motor abilities in 60 children 8-13 years old (M=10.43±1.63 years) and to identify the relationship between these abilities and performance in fundamental basketball skills. Simple reaction time, whole body reaction time, depth perception and coincidence anticipation timing were the perceptual abilities, whereas dynamic balance, wrist-finger dexterity, kinesthesis and whole body movement time were the motor abilities that were examined in this study. The AAHPERD basketball test for passing, dribble and shooting was used to evaluate performance in the respective basketball skills. According to the results, there was a significant age effect on the evaluated abilities (p<.05). Regarding the relationship among abilities and skills, a significant correlation was depicted between wrist-finger dexterity, whole body reaction and movement time, and performance in basketball skills for all age groups (p<.05). Furthermore, kinesthesis was correlated with dribble and shooting performance (p<.05), while depth perception was significantly correlated with shooting performance (p<.05). These findings can support any effort to detect performance variations and provide comprehensive interventions that will lead to further performance and learning enhancement through deliberate practice.